Making Senses of Appetite, Love and Lust in "Io Sono L’Amore" (2009) - Caetano, Joana (Cadernos de Literatura Comparada (teste), 2017)
"Sensation is fundamental to our experience of the world. Shaped by culture, gender, and class, the senses mediate between mind and body, idea and object, self and environment." (The Senses and the Society Journal) After centuries of what one might call "the religion of reason”, during which the senses, the body and the life of emotions have been mistreated and repressed, we are witnessing a return of subjectivism and its reactions regarding identity. The quotation above points to a theory in Cultural Studies that has recently emerged in academia: Sensory Studies. According to this approach, the senses are essential to the human experience of reality and the understanding of the world: more than employing their senses and being shaped by them, human beings construct them. At the heart of Sensory Studies is the thesis of the mediatory role of senses in the production of experience. Since, as Laplantine claims, cinema is made up of "permanently transforming sensations," films can be the ideal means to think sensually. Inspired by this view and the theory that bodies are not simple objects of thought nor are they fixed into their own boundaries (cf. J. Butler), this paper will focus on the analysis of the Italian film Io Sono L’Amore (2009) by Luca Guadagnino. Although the film seems to depict a common story, it is, in fact, a deeply stylized narrative of the senses – an aestheticization of everyday life and a utopian construal of the body. Applying conceptual tools from both Sensory Studies and Food Studies, we will travel through Emma Recchi's physical and emotional journey of delight, and try to comprehend how fine food can lead to desire, the pleasures of the flesh and a more profound knowledge of oneself.